Meningkatkan Kualitas Pelayanan di Bank Syariah: Penelitian dengan Fuzzy Servqual dan Dimensi Carter - Astuti, Septin Puji; Utami, Datien Eriska; Wilasari, Wiwik (Universitas Prasetiya Mulya, 2009)
SERVQUAL was appliedin this study for measuring service quality in Shariah Bank Rakyat Indonesia (BRIS). Due toits shariah characteristic, compliance dimension was integrated into SERVQUAL dimensions and fuzzy theory was integrated for assessing the perception and expectation of customers.T statistic test and GLM modeling was applied to test the significant of the gaps of each item and to understand the dimensions which has more contribution to service quality of the bank.From this research, concludes that the gap was significant statistically. Furthermore, tangibilitydimension was the worst quality of BRIS, but empathy is the best quality